Uncertainty management via online scheduling for optimal short-term operation of cascaded hydropower systems. (4th March 2020) - Mathur, Pulkit; Swartz, Christopher L.E.; Zyngier, Danielle; Welt, Francois
Highlights: Novel scheme for online scheduling of cascaded hydropower systems. Electricity price, inflow and model parameter uncertainty mitigated via feedback. Both continuous and discrete decisions modeled within online scheduling framework. "Nervousness" issue quantitatively analyzed in the context of online scheduling. Nervousness mitigation strategies developed and implemented. Abstract: The efficient utilization of available resources plays a significant role in the operation of cascaded hydropower systems. Scheduling of such systems may be used to determine power generation and generating unit decisions that optimize economic performance subject to prevailing constraints. The highly volatile and unpredictable nature of market and weather conditions give rise to uncertainties in electricity prices and water inflows, which may significantly impact the power generation schedules for these systems. Computed schedules may also give rise to significant variation in the generating unit commitments in response to slight fluctuations in electricity pricing, a phenomenon referred to as "nervousness". This article focuses on the development and implementation of a novel rolling horizon online scheduling scheme capable of handling uncertainties in key system and model parameters. Different strategies for mitigating the undesirable effects of nervousness are also investigated. These approaches are demonstrated through application to several case studies.